Inhibition of Candida albicans in vivo and in vitro by antimicrobial peptides chromogranin A-N12 through microRNA-155/suppressor of cytokine signaling 1 axis. Issue 2 (1st February 2022) - Li, Xiaohua; Hu, Qun; Lin, Qiong; Luo, Jianxiong; Xu, Junping; Chen, Lifang; Xu, Liyu; Lin, Xin
ABSTRACT: Antimicrobial peptides (AMPs) have proven to inhibit a variety of pathogens. Chromogranin A-N12 (CGA-N12) is a kind of AMP, and it is characterized by stable structure, high anti-Candida activity, and good safety. However, it remains unclear whether CGA-N12 could effectively inhibit the growth of Candida albicans (C. albicans) . Colony forming assays were used to measure minimal inhibitory concentration (MIC), minimal fungicidal concentration (MFC), and time-kill curve. Disseminated C. albicans rabbit model was established to investigate the influence of CGA-N12 on histological damage. The protein and mRNA levels of suppressor of cytokine signaling 1 (SOCS1) after treatment were investigated. The MIC and MFC of CGA-N12 against C. albicans was 6 mg/mL. CGA-N12 considerably inhibited germ tube formation of C. albicans . The fungal load in the tissues and inflammatory factors in the serum were suppressed by CGA-N12. CGA-N12 significantly reduced the histological changes caused by C. albicans, and the protein and mRNA levels of SOCS1 were markedly inhibited. The inhibition effect of CGA-N12 on C. albicans and significant improvement of histological damage by CGA-N12 through microRNA-155/SOCS1 axis were proved in this study. This study proposes a novel therapeutic strategy for the treatment and prevention of C. albicans . Abbreviations: AMPs: Antimicrobial peptides; MIC: Minimal inhibitory concentration; MFC: Minimal fungicidal concentration; AIDS: Acquired immune deficiency syndrome; PBS: Phosphate buffer saline; FBS: Fetal bovine serum; ROS: Reactive oxygen species; CFU: Colony formation unit; CGA: Chromogranin A; SOCS1: Suppressor of cytokine signaling 1; SDA: Sabouraud Dextrose Agar; GRAVY: Grand average of hydropathicity; C. parapsilosis: Candida parapsilosis; C. albicans: Candida albicans